2018
DOI: 10.1080/14767058.2018.1514377
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound predictors of candidates for segmental resection in pregnants with placenta accreta

Abstract: Our data showed that among some sonographic findings of abnormal placentation, smallest myometrial thickness was a significant predictor to determine candidates for conservative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…However, a retrospective review of 43 women with pregnancies involving PAS who underwent uterine wall resection showed that sonographic retroplacental myometrial thickness was significantly predictive of success of uterine wall resection. A thin myometrial thickness with a cut‐off of 1.6 mm yielded sensitivity, specificity, and AUC of 94%, 85%, and 0.91, respectively 15 . Although PAS type is principally an intraoperative diagnosis, prediction of degree of placental invasion can be satisfactorily reached by conventional ultrasound 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a retrospective review of 43 women with pregnancies involving PAS who underwent uterine wall resection showed that sonographic retroplacental myometrial thickness was significantly predictive of success of uterine wall resection. A thin myometrial thickness with a cut‐off of 1.6 mm yielded sensitivity, specificity, and AUC of 94%, 85%, and 0.91, respectively 15 . Although PAS type is principally an intraoperative diagnosis, prediction of degree of placental invasion can be satisfactorily reached by conventional ultrasound 16 …”
Section: Discussionmentioning
confidence: 99%
“…A thin myometrial thickness with a cut-off of 1.6 mm yielded sensitivity, specificity, and AUC of 94%, 85%, and 0.91, respectively. 15 Although PAS type is principally an intraoperative diagnosis, prediction of degree of placental invasion can be satisfactorily reached by conventional ultrasound. 16 To our knowledge, the current study may present the first international multicenter study that investigates clinical outcomes of uterus-preserving management of PAS.…”
Section: Multivariable Logistic Regression (All Variables) P Valuementioning
confidence: 99%
“…Nevertheless, PAS is still not recognized prenatally in a percentage of cases ranging from 50–70% [ 22 ]. Many studies published so far have proposed different ultrasonographic signs evocative of PAS [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Anyway, these studies frequently use the same descriptors with different names or, on the contrary, the same definition has been used for different finds.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, many studies have proposed different diagnostic scores for PAS based upon ultrasonographic signs and/or clinical information with the purpose of predicting and diagnosing PAS and maternal-neonatal outcome [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, the performances of these scores have shown considerable variability among all studies.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies on conservative treatment in cases of placenta accreta spectrum (PAS) disorder. 6 7 8 9 10 11 Unfortunately, there is no randomized controlled study that compares hysterectomy and conservative methods according to maternal morbidity, bleeding and complications in cases of PAS disorder. It is not yet possible to say that the conservative method would increase the risk of bleeding and the morbidity of the patient.…”
Section: Authors' Replymentioning
confidence: 99%